Flowering biology and breeding system of Ardisia humilis - Jiatong YE; Shizhong MAO; Xinghua HU; Xiaozhen ZHU; Yunbo DUAN; Tao DENG; Shixun HUANG (Guangxi Zhiwu, 2023)
Ardisia humilis is an excellent wild ornamental plant. For the purpose of fully utilization of this elite germplasm, the flowering biology and breeding system of this plant were explored in this study. We conducted field investigation in the flowering phenology, flower-visiting insect and their visiting behaviors on A. humilis individuals introduced in homogeneous garden. Furthermore, pollen viability and stigma receptivity were detected by pollen germination in vitro and benzidine-hydrogen peroxide method, respectively. Combined with artificial pollination, the self-compatibility and the self-pollination of A. humilis were also analyzed in this study. The results were as follows: (1) The florescence of A. humilis was from mid-late May to early June, and the full flowering period was at the end of May. The flowering period of the population, single plant and single flower were approximately 25 d, 17-20 d and 1 d, respectively. (2) A. humilis developed protogynic bisexual flowers, the pistil ripened first with partial overlaps on mature stage of pistil and that of stamen, while stigma remained receptivity until 1 d after stamens fall. (3) With the out-crossing index (OCI) value of 4 and pollen / ovule value of 5.61×103, the breeding system of A. humilis was considered to be outcrossing with partial self-compatibility, and the pollinator insects were essential. (4) The seed set of natural pollination ranked the highest level (average 52.96%), followed by that of autogamy (52.29%) and of artificial-cross pollination (50.33%), with no significant differences among the three (P>0.05), but significantly higher than that of artificial geitonogamy (28.67%) (P<0.05). This study indicated that, beside of being excellent flowering plant, A. humilis not only had a strong outcrossing affinity, but also had a strong autogamy ability. (5) Lasioglossum sp. 1, Lasioglossum sp. 2 and Halictus sp. were the most observed floral visitors on Ardisia humilis. This study provides an important theoretical reference for the resource utilization and germplasm innovation of A. humilis.